TINDAK TUTUR KONSUMEN DALAM ULASAN PLATFORM E-COMMERCE - Pratama, Aditya; Utami, Wanda Yulia (Teks: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2023)
Consumers who are dissatisfied tend to often share negative messages through review forums. This will have a serious impact on seller performance and profitability. Complaints from online buyers should be considered as an opportunity to improve quality or restore service for sellers (sellers). This research aims to determine the form of speech acts in e-commerce platform reviews. The method used in this research is a qualitative descriptive method with a phenomenological design. The results of this research reveal that there are 3 forms of speech acts from the 15 speech data used as study material. Based on the description of the research findings, it was found that assertive speech acts took the form of complaints; directive speech acts in the form of requests; and expressive speech acts in the form of praise.